Application of the Problem Based Learning Learning Model to Improve the Mathematical Problem Solving Ability of State Junior High School Students 4 Hilissekai for the 2021/2022 Academic Year - Salima Zai; Ratna Natalia Mendrofa; Yulisman Zega (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The Problem Based Learning learning model is an innovative learning model that can provide active learning conditions to students. The distinctive feature of this learning model is that it involves students to solve a problem through the stages of the scientific method so that students can learn knowledge related to the problem and at the same time have the skills to solve problems. The research objectives were: (1) to describe the quality of learning mathematics through the Problem Based Learning model at SMP Negeri 4 Hiliserangkai. (2) Describe student learning outcomes in mathematics, especially problem solving through the Problem Based Learning model at SMP Negeri 4 Hiliserangkai. This research was conducted in class VIII of SMP Negeri 4 Hiliserangkai semester 1 of the 2021/2022 academic year with a total of 20 students. Based on the results of this study, the average quality of student learning in cycle I was 57.35%, which was classified as poor, while in cycle II, 79.41% was classified as good. And the average student learning outcomes in the first cycle is 62.5% in the sufficient category, and in the second cycle is 81.61% in the good category, this has reached the target set at 75%.